2019
DOI: 10.1021/acs.nanolett.9b02376
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Assembly of Viruslike Nucleocapsids Elucidated at the Single-Particle Level

Abstract: While the structure of a multitude of viral particles has been resolved to atomistic detail, their assembly pathways remain largely elusive. Key unresolved issues are particle nucleation, particle growth, and the mode of genome compaction. These issues are difficult to address in bulk approaches and are effectively only accessible by the real-time tracking of assembly dynamics of individual particles. This we do here by studying the assembly into rod-shaped viruslike particles (VLPs) of artificial capsid polyp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…Note that in earlier papers we have shown that VLP lengths obtained using AFM on dried complexes are consistent with those obtained using other methods, in particular, cryo-electron microscopy and static light scattering, 7 as well as AFM in liquid. 20…”
Section: Resultsmentioning
confidence: 99%
“…Note that in earlier papers we have shown that VLP lengths obtained using AFM on dried complexes are consistent with those obtained using other methods, in particular, cryo-electron microscopy and static light scattering, 7 as well as AFM in liquid. 20…”
Section: Resultsmentioning
confidence: 99%
“…In a different single-particle approach, a dsDNA strand was stretched between two beads in a double optical tweezers set-up 72 and then exposed to a solution of fluorescently labelled synthetic polypeptide strands, which played the role of model capsid proteins. Different assembly stages of the resulting VLP were visualized in real time with millisecond temporal resolution (Fig.…”
Section: Viral Self-assembly Dynamicsmentioning
confidence: 99%
“…Optical tweezers adapted with permission from ref. 72 . Interferometric scattering microscopy adapted with permission from ref.…”
mentioning
confidence: 99%
“…The dual‐trap optical tweezers with 3‐color confocal fluorescence microscopy set‐up [ 28 ] (C‐trap, LUMICKS, Amsterdam, The Netherlands), was used for the single‐cell kinetic experiments. A 5‐channel microfluidic cell (LUMICKS) mounted on an automated XY‐stage was used to isolate individual cells under different conditions.…”
Section: Methodsmentioning
confidence: 99%